Peran Komunikasi Dalam Menyelesaikan Konflik Organisasi Di SMK Triguna 1956 - Moh Fariz Dzikrul Kholik; Farhan Arif Alfarisi; Ahmad Syaifullah; Moh Abdullah Azzam Al-Amiin (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the Role of Communication in Resolving Organizational Conflict. This research was conducted on students who served as Student Council at Triguna Vocational School. The research method used is interviews and literature review. The results of this study say that communication plays an important role in resolving conflicts in the organization. The sample shows that without good communication it can lead to miscommunication and misunderstanding among members of the organization. Therefore, the five elements of communication must be maximized properly so that conflicts do not occur in the organization.